2023
DOI: 10.1038/s41594-023-01184-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural organization of the retriever–CCC endosomal recycling complex

Daniel J. Boesch,
Amika Singla,
Yan Han
et al.

Abstract: The recycling of membrane proteins from endosomes to the cell surface is vital for cell signaling and survival. Retriever, a trimeric complex of VPS35L, VPS26C and VPS29, together with the CCC complex comprising CCDC22, CCDC93, and COMMD proteins, plays a crucial role in this process. The precise mechanisms underlying Retriever assembly and its interaction with CCC have remained elusive. Here, we present the first high-resolution structure of Retriever determined using cryogenic electron microscopy. The struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Consistently, DENND10 knockout was phenotypically similar to Rab27a knockdown cells in multiple aspects, including accumulation of lysosomal proteins [ 49 ], reduction of EV release [ 50 ], and impaired migration [ 48 ]. Additionally, several recent structural studies [ 12 14 ] identified DENND10 as an integral subunit of the CCC-Retriever (Commander) endosomal complexes, a highly conserved protein machinery involved in endosomal sorting and recycling [ 51 , 52 ]. We have confirmed this interaction ourselves (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, DENND10 knockout was phenotypically similar to Rab27a knockdown cells in multiple aspects, including accumulation of lysosomal proteins [ 49 ], reduction of EV release [ 50 ], and impaired migration [ 48 ]. Additionally, several recent structural studies [ 12 14 ] identified DENND10 as an integral subunit of the CCC-Retriever (Commander) endosomal complexes, a highly conserved protein machinery involved in endosomal sorting and recycling [ 51 , 52 ]. We have confirmed this interaction ourselves (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…Human DENND10 protein shares 69.0% sequence similarity with its orthologue in amoeba ( Dictyostelium discoideum ) [ 11 ], suggesting conserved function(s) from unicellular organisms to vertebrates. Several recent structural studies have demonstrated that DENND10 is an integral subunit within the CCC/Retriever complexes (also called the Commander complex) in the endosomal recycling pathway [ 12 14 ]. However, no physiological roles for DENND10 have been described so far.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 11, 2024. ; https://doi.org/10.1101/2024.01.10.574988 doi: bioRxiv preprint Retriever is assembled around a central VPS35L subunit to which VPS26C and VPS29 associate at spatially distant amino-and carboxy-terminal regions of the VPS35L asolenoid (Fig. 1B) (Boesch et al, 2023;Healy et al, 2023;Laulumaa et al, 2023). We employed AlphaFold2 modelling (Jumper et al, 2021;Mirdita et al, 2022) to predict the association between Retriever and the unstructured human SNX17 tail corresponding to residues Gly400-to-Leu470.…”
Section: Snx17 Associates With Commander Via Its Extended C-terminal ...mentioning
confidence: 99%
“…Central to network function are multi-protein complexes that coordinate sequence-dependent recognition of integral proteins with the biogenesis of vesicular and tubular transport carriers (McNally and Cullen, 2018; Chen et al, 2019; McDonald, 2021). Retriever is an essential cargo sorting complex and is a stable heterotrimer of VPS26C, VPS35L and VPS29, that together with the dodecameric CCDC22, CCDC93, COMMD (CCC) complex and DENND10, forms the 16-subunit Commander super-assembly (Phillips-Krawczak et al, 2015; Mallam and Marcotte, 2017; McNally et al, 2017; Boesch et al, 2023; Healy et al, 2023; Laulumaa et al, 2023). Defects in Commander assembly and function are associated with metabolic disorders including hypercholesterolemia (Bartuzi et al, 2016; Fedoseienko et al, 2018; Rimbert et al, 2020; Vos et al, 2023), viral infection (Daniloski et al, 2021; Zhu et al, 2021), and lead to Ritscher-Schinzel syndrome, a multi-system developmental disorder characterized by abnormal craniofacial features, cerebellar hypoplasia, and stunted cardiovascular development (Kolanczyk et al, 2015; Kato et al, 2020; Otsuji et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…• Clathrin. Another small network included the clathrin interactor 1 (CLINT1), clathrin light chain beta (CLTB), and aftiphilin (AFTPH) (Table 2 and S3) [37,38,[51][52][53][54][55][56][57][58][59][60][61][62][63][64]. Clathrinmediated endocytosis is important for cellular nutrition as well as receptor-mediated endocytosis, membrane recycling, and control of signal pathways [26,30].…”
mentioning
confidence: 99%